2011
DOI: 10.2474/trol.6.45
|View full text |Cite
|
Sign up to set email alerts
|

New Life Prediction Method of the Grease by the Activation Energy

Abstract: This paper proposes a new grease life predicting method which utilizes kinetics analysis of measured data obtained through thermogravimetry. The grease life is predicted by weight loss at a certain temperature. By separating effects of complex dynamics and physics in ball bearings to which the grease is applied, a static life of the grease can be predicted as a stand-alone evaluation within very short period of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A decrease in the yield stress of the lithium grease at elevated temperature was reported in Reference [19]. Ide et al [20] found the activation energy based on Arrhenius's law as an appropriate parameter for life prediction of lithium greases.…”
Section: Degradation Systems Of Greasesmentioning
confidence: 90%
“…A decrease in the yield stress of the lithium grease at elevated temperature was reported in Reference [19]. Ide et al [20] found the activation energy based on Arrhenius's law as an appropriate parameter for life prediction of lithium greases.…”
Section: Degradation Systems Of Greasesmentioning
confidence: 90%
“…A decrease in grease yield stress at higher temperature was also shown by Karis,et al (16), Gow (17), and Froishterer (18). Ide, et al (19) predicted the grease life of lithium soap-thickened grease using thermogravimetry tests. They concluded that the activation energy based on Arrhenius's law is an appropriate parameter in grease life prediction.…”
Section: Introductionmentioning
confidence: 99%